2017
DOI: 10.1016/j.jobcr.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Miracle cells for natural dentistry – A review

Abstract: Stem cells are undifferentiated cells that can differentiate into specialized cells. Recently, enormous growth has been seen in the recognition of stem cell-based therapies, which have the potential to ameliorate the life of patients with conditions that span from Parkinson's disease to cardiac ischemia to bone or tooth loss. This research has produced new but unexplored possibilities in the regeneration of different organs and tissues. Presently, research is focused on the proficiency of stem cells and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Dental pulp MSCs have been studied in animal models of different diseases (2), including systemic lupus erythematosus, ischemic brain injury, spinal cord injury, and muscular atrophy. Stem cells from human exfoliated deciduous teeth (SHED) were shown to differentiate into insulin-secreting cells in vitro (3), and may be potentially useful for the treatment of glucose metabolic disorders.…”
Section: ' Introductionmentioning
confidence: 99%
“…Dental pulp MSCs have been studied in animal models of different diseases (2), including systemic lupus erythematosus, ischemic brain injury, spinal cord injury, and muscular atrophy. Stem cells from human exfoliated deciduous teeth (SHED) were shown to differentiate into insulin-secreting cells in vitro (3), and may be potentially useful for the treatment of glucose metabolic disorders.…”
Section: ' Introductionmentioning
confidence: 99%
“…Studies on TGPCs have demonstrated their high proliferation activity and capacity to differentiation into adipogenic, chondrogenic, osteogenic, odontogenic, and neurogenic tissue [ 28 , 29 ]. In addition, TGPCs can differentiate into hepatocytes in vitro [ 25 , 30 ] and are able to form tube-like structures, possibly evidence of vascularization [ 31 ]. Stem cells of human exfoliated deciduous teeth (SHEDs), obtained from exfoliated deciduous teeth, have higher proliferation capacity than DPSCs and the capability to differentiate into many more different body tissues than other types of SCs, including into adipocytes, osteoblasts, odontoblasts, neural cells, hepatocytes, and endothelial cells.…”
Section: Stem Cells Biomaterials and Scaffolds For Oral Tissue Ementioning
confidence: 99%
“…SCs collected from postnatal tooth buds of animals, self-replicated and differentiated in vitro, have been seeded onto a biodegradable scaffold. Their in vivo maturation was achieved by transplanting the seeded scaffolds either into the renal capsule or the omentum, followed by their reimplantation into an extracted tooth place or the jaw [ 31 ]. However, by using non-human cells, the chance of immune rejection exists [ 306 ].…”
Section: Regenerative Therapies In Dentistry—potential Clinical Apmentioning
confidence: 99%
See 1 more Smart Citation